Case Report: Prenatal Diagnosis of a Novel Variant c.251dupT (p.N87Kfs*6) in BCOR Resulting in Oculofaciocardiodental Syndrome Using Whole-Exome Sequencing - Zhuang, Jianlong; Chen, Chunnuan; Chen, Yu’e; Zeng, Shuhong; Jiang, Yuying; Wang, Yuanbai; Chen, Xinying; Xie, Yingjun; Wang, Gaoxiong (Frontiers in Genetics, 2022)
Background: Oculofaciocardiodental (OFCD) syndrome is an X-linked dominant syndrome caused by BCOR variants, which manifests only in females; it is presumed leading to male lethality. Herein, we aim to present a prenatal diagnosis for OFCD syndrome associate with a novel hemizygous variant in BCOR gene. Case presentation: A 29-year-old pregnant woman from Quanzhou Fujian province, China with fetal ultrasound anomalies was enrolled in this study. Amniocentesis was undergone for prenatal diagnosis in the gestational age of 19+2 weeks of the pregnancy. None of chromosomal abnormalities was identified by karyotype and chromosomal microarray analysis. Further whole exome sequencing (WES) detection result demonstrated a novel hemizygous variant of c.251dupT (p.N87Kfs*6) in BCOR gene was identified in the fetus, which was a frameshift mutation and classified as likely pathogenic variant, may lead to OFCD according to the clinical feature of the fetus. Parental verification indicated that the variant in BCOR gene was inherited from his mother who exhibit clinical feature associate with OFCD syndrome. Conclusions: A prenatal diagnosis analysis of male fetus with novel variant in BCOR that leading to OFCD was first reported. Our study broadened the spectrum of BCOR result in OFCD and provided valuable reference for prenatal genetic consultation.